Problem krivde pri Ojdipu in Josefu K. - Vrečko, Janez (Keria (Ljubljana), 2002)
The issue under discussion is the hamartia of Oedipus and Joseph K. Originally a fateful error on the part of the hero, it later takes shape as his response to the situation in which he finds himself. But while Oedipus is led to self-punishment as a consequence, Joseph is put to a brutal death. Both heroes experience anagnorisis, and a significant role on their way is played by women, the prophet Teiresias, and the priest in the Cathedral. A comparison of Oedipus' death at Colonus and Joseph's death in the quarry reveals the underlying notions of ritual purity, the dissolution of the ritual, and the difference between fatality and hopefulness.
Keywords: hamartija; Kafka, Franz; Kafka, Franz: Proces; krivda; primerjalna književnost; Sophocles; Sophocles: Kralj Ojdip; starogrška tragedija